The Adoption of Multiplayer Online Battle Arena to Introduce Wayang Character - Andre Andre (Bina Nusantara University, 2021)
Wayang is considered a cultural heritage that has been passed down from generation to generation in Indonesia. However, the younger generation known as digital natives shows a lack of motivation and interest in Wayang. Therefore, it became an important matter to introduce traditional Wayang to younger audiences in engaging formats. This paper proposes an adaptation of the multiplayer online battle arena or known as MOBA. This type of multiplayer game for the mobile market is gaining high popularity among the young generation because it embraces quick-paced, strategic, and intense battle scenes. We called our game